Zulu - Levine, Joseph E.; Baker, Stanley, Sir, 1928-1976.; Endfield, Cy.; Prebble, John, 1915-; Hawkins, Jack, 1910-1973.; Jacobsson, Ulla, 1929-1982.; Booth, James, 1933-; Caine, Michael; Dade, Stephen; Jympson, John.; Barry, John, 1933-; Embassy Pictures Corp.; et al. (Woodland Hills, CA : Westlake Entertainment Group, 2003)
Zulu is set in Africa in 1879 only hours after the battle of Isandhlwana. A small group of British soldiers stood their ground at a farm house against an onslaught of wave after wave of Zulus.
Not rated.
DVD release of the 1964 motion picture
Original screenplay by John Prebble and Cy Endfield ; director of photography, Stephen Dade ; editor, John Jympson ; music, John Barry.
Stanley Baker, Jack Hawkins, Ulla Jacobsson, James Booth, Michael Caine.
85099
Keywords: Zulu War, 1879 -- Drama; Feature films